One-dimensional man : studies in the ideology of advanced industrial society - Marcuse, Herbert (London : Routledge, 2002)
One of the most important texts of modern times, Herbert Marcuse's analysis and image of a one-dimensional man in a one-dimensional society has shaped many young radical's way of seeing and experiencing life.
ENH
Karim International
Keywords: Social sciences -- Philosophy; Civilization, Modern; English language